Optimization, validation, and comparison of a rapid method for the quantification of insulin‐like growth factor 1 in serum using liquid chromatography–high‐resolution mass spectrometry. Issue 2 (26th October 2020) - Seo, Yoondam; Park, Jisoo; Kim, Minyoung; Sung, Changmin; Kwon, Oh‐Seung; Lee, Hwa Jeong; Min, Hophil
Abstract: Human insulin‐like growth factor 1 (IGF‐I) is the primary mediator of the effects of the growth hormone (GH). Therefore, it has been used as a biomarker to detect the abuse of GH in sports. The measurement of IGF‐I relies on mass‐based and immunological approaches to analysis. Among the mass‐based analysis methods, liquid chromatography–mass spectrometry (LC–MS) has a number of functional advantages. LC–MS measurements based on the quantification of IGF‐I, according to trypsin digestion, are used in the most common method of analyzing doping. However, this method is time‐consuming and subject to experimental variability. In this study, we optimized a rapid method for detecting IGF‐I without the trypsin digestion step. This method of analysis uses an ultra‐centrifugal filter and an LC‐HRMS through narrow‐range mass scan method. To verify the validity of this method, eight categories of validation testing were applied with the following results: linearity, R 2 > 0.99; limit of detection, 15 ng/ml; limit of quantification, 20 ng/ml; accuracy, >99%; recovery rate, >95%; carryover, <0.03; and inter‐ and intra‐day precision values, %CV < 2% and %CV < 6%, respectively. Furthermore, we discussed the correlation of the quantified concentration from two other methods, immunoradiometric assay (IRMA) and parallel reaction monitoring method, using 209 serum samples. In conclusion, although both mass spectrometry‐based methods worked equally well in terms of analytical performance and correlation with IRMA results, narrow‐range mass scan method had several advantages, such as time and cost savings and reliable reproducibility, over the existing methods. Abstract : The narrow‐range scan mode method with HRMS of analysis intact IGF‐1 eliminates processes such as trypsin digestion, immunoaffinity, and solid phase extraction and requires relatively low volume samples. The method was designed, optimized, validated, and highly compatible with existing methods.